A new species of Stenchaetothrips (Thysanoptera, Thripidae) from Bamboo, based on morphological and molecular data - Mound, Laurence A.; Gunawardana, Disna N.; Li, Dongmei (Zootaxa, 2017)
Stenchaetothrips martini sp.n. is distinguished from related species on morphological and molecular character states. It is the eleventh species in this genus to be recorded from a species of bamboo, but only the fourth of these 11 species to have a prominent spinula on the mesothoracic furca. Described here from New Zealand, this thrips is presumably introduced from Southeast Asia, together with its host plant, Phyllostachys aurea.